A Complement Type to SRS-Schwab Adult Spinal Deformity Classification: The Failure of Pelvic Compensation. Issue 18 (30th June 2022) - Kwon, Ohsang; Lee, Sanghoon; Park, Sang-Min; Yeom, Jin S.; Kim, Ho-Joong
Abstract : Study Design: Retrospective review. Objective: To determine characteristics of patients with adult spinal deformity (ASD) who showed failed pelvic compensation even with significant sagittal imbalance. Background: Patients who show failed pelvic compensation despite significant sagittal imbalance reportedly present distinct clinical outcomes. However, to our knowledge, no study has clearly defined or characterized this subgroup of patients with ASD. Materials and Methods: We examined 126 patients who underwent reconstructive spinal surgery for ASD between September 2016 and September 2020. Radiographic spinopelvic parameters were assessed. The patients were divided into four quadrant groups based on the two axes of pelvic tilt/pelvic incidence (PT/PI) and the sagittal vertical axis (SVA) with reference to the population median values (0.68 and 147.5 mm, respectively). Patients with low PT/PI and high SVA were considered to have failed pelvic compensation, and they were compared with other patient groups. Results: Patients with failed pelvic compensation (low PT/PI and high SVA) had worse clinical outcomes than those with successful pelvic compensation (high PT/PI and high SVA) at one year after surgery. Regarding radiographic outcomes, patients with failed pelvic compensation showed a significantly larger postoperative SVA even after correcting the PI−lumbar lordosis mismatch was corrected to a comparable range with the group of successful pelvic compensation. Notably, patients with failed pelvic compensation showed larger cross-sectional areas of the psoas and back extensor muscles than those with successful pelvic compensation. This suggests that failure of pelvic compensation did not occur because of back muscle weakness, which implies another underlying pathophysiology, including neurological origin. Conclusion: Compared with patients with successful pelvic compensation, those with failed pelvic compensation showed lower postoperative improvements in clinical and radiographic outcomes. Therefore, it is important to consider pelvic compensation when planning surgical correction of deformities. Distinct surgical approaches, including overcorrection of the PI−lumbar lordosis mismatch or global sagittal alignment, should be attempted to ensure postoperative symptom improvement.